Exposure to type 2 diabetes provokes mitochondrial impairment in apparently healthy human hearts - Zweck, Elric; Scheiber, Daniel; Jelenik, Tomas; Bönner, Florian; Horn, Patrick; Pesta, Dominik; Schultheiss, Heinz-Peter; Boeken, Udo; Akhyari, Payam; Lichtenberg, Artur; Kelm, Malte; Roden, Michael; et al. (Diabetes care, 2021)
Cardiac mitochondrial alterations are suspected to play a key role in the development of diabetes-related heart failure as reported in some animal and few human studies in type 2 diabetes (1). It is yet unclear whether these alterations are induced by diabetes-related metabolic changes or develop secondary to other factors underlying heart failure including micro- and macrovascular disease. We hypothesized that 1) exposure to type 2 diabetes provokes myocardial mitochondrial impairment prior to apparent left ventricular heart failure in humans and 2) these mitochondrial alterations are accompanied by increased oxidative stress, edema, and intracellular inflammation.
Gesehen am 28.02.2022